Pengaruh Kualitas Produk dan Kepuasan Pelayanan terhadap Minat Berlangganan Internet Service Provider - Janah, Anissatul; Zakaria, Zahra (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to determine the effect of product quality and service satisfaction on interest in subscribing to Internet Service Providers (Case Study on AMNET Subnet in Tridaya Sakti Village, Sasak Tiga Village). This research applies a type of quantitative research. This research technique is a probability sampling method,where everyone who is a member of the population has the same opportunity to become a respondent. While the sample selection is based on random sampling technique, which is simple random. The sample in this study was 60 respondents. The population in this study are respondents who have bought products or who use AMNET internet services as many as 150 in Tridaya Sakti Village, Sasak Tiga Village, South Tambun District, Bekasi Regency. This research analysis is multiple linear regression analysis using SPSS 25 for Windows software. Data collected using questionnaires distributed via Google Form, interview, and documentation. The results of this study indicate that Product Quality has a partial effect on Subscription Interest. Service Satisfaction has a partial effect on Subscription Interest. Product Quality and Service Satisfaction simultaneously affect Subscription Interest.